2014
DOI: 10.4049/jimmunol.1301319
|View full text |Cite
|
Sign up to set email alerts
|

IFN Priming Is Necessary but Not Sufficient To Turn on a Migratory Dendritic Cell Program in Lupus Monocytes

Abstract: Blood monocytes from children with systemic lupus erythematosus (SLE) behave like dendritic cells (DCs), and SLE serum induces healthy monocytes to differentiate into DCs in a type I Interferon (IFN)-dependent manner. Here, we found that these monocytes display significant transcriptional changes, including a prominent IFN signature, compared to healthy controls. Few of those changes, however, explain DC function. Exposure to allogeneic T cells in vitro reprograms SLE monocytes to acquire DC phenotype and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 69 publications
2
29
0
Order By: Relevance
“…Remarkably, despite the variability in organ system involvement, inflammatory marker values, autoantibody profile, and SLEDAI scores in the clinically heterogeneous pediatric SLE patients studied (Table 1), the monocyte cytokine signature (MCP1/Mip1β/IL-1RA) was observed in every patient. Consistent with previous literature, we demonstrated that monocytes from SLE patients and healthy controls did no exhibit phenotypic or population frequency differences [63] (Figure 2, Figure S2). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Remarkably, despite the variability in organ system involvement, inflammatory marker values, autoantibody profile, and SLEDAI scores in the clinically heterogeneous pediatric SLE patients studied (Table 1), the monocyte cytokine signature (MCP1/Mip1β/IL-1RA) was observed in every patient. Consistent with previous literature, we demonstrated that monocytes from SLE patients and healthy controls did no exhibit phenotypic or population frequency differences [63] (Figure 2, Figure S2). …”
Section: Discussionsupporting
confidence: 92%
“…We found that the cytokine signature was induced in CD14 hi monocytes from healthy donors after incubation with SLE patient plasma, but not with age and sex-matched control plasma (Figure 3). While stimulation of healthy donor cells with SLE plasma has been previously demonstrated to induce monocyte apoptosis [67], monocyte differentiation into dendritic cells [63], stimulate IL-10 and IL-6 production by PBMCs [22], and induce transcription of IFN responsive genes [21,68], SLE plasma had not been shown to induce MCP1, Mip1β, and IL-1RA production by healthy CD14 hi monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DCs associated to T-cell and B-cell aggregates are believed to undergo a local maturation process that can perpetuate T cell activation in the lymphocytic aggregates observed in these diseases [124,125]. By contrast, IFN-a priming and LPS stimulation significantly upregulated CCR7 in moDCs from SLE patients [128]. Similarly, immune complexes upregulated CCR7 and increased dermal DC migration in a mouse model of SLE [129].…”
Section: Cdc Recruitmentmentioning
confidence: 99%
“…We therefore utilized the well-accepted model of human DC differentiation from peripheral blood monocytes under inflammatory conditions, which is a useful tool to study DC functions ex vivo [1416]. Pathogenic inflammation can trigger SLE disease exacerbations [17, 18], in which Toll-like receptor 4 (TLR4) and TLR4 responsiveness are important [19]. We therefore choose LPS-activated moDCs as a subtype of DCs generated upon inflammation.…”
Section: Introductionmentioning
confidence: 99%